1990
DOI: 10.1139/m90-026
|View full text |Cite
|
Sign up to set email alerts
|

Receptors for transferrin in pathogenic bacteria are specific for the host's protein

Abstract: Transferrin receptors detected by a solid-phase binding assay were shown to be specific for the host's transferrin in the representative bacterial pathogens Neisseria meningitidis (human), Pasteurella haemolytica (bovine), and Actinobacillus pleuropneumoniae (porcine). Consistent with the receptor specificity, iron-deficient bacteria were only capable of utilizing transferrin from the host as a source of iron for growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 5 publications
2
54
0
1
Order By: Relevance
“…Even though there is considerable homology between the transferrins, such as porcine, bovine, sheep, and ovotransferrin, N. meningitidis can discriminate against these non-human-derived transferrins (85,141,144). This correlates well with the role of N. meningitidis as an obligate human pathogen.…”
Section: Iron Availability In the Human Hostmentioning
confidence: 82%
“…Even though there is considerable homology between the transferrins, such as porcine, bovine, sheep, and ovotransferrin, N. meningitidis can discriminate against these non-human-derived transferrins (85,141,144). This correlates well with the role of N. meningitidis as an obligate human pathogen.…”
Section: Iron Availability In the Human Hostmentioning
confidence: 82%
“…Up to now, to our knowledge, it has been reported that bacterial Tf receptors have a strict host specificity and that they bind only Tf from their particular host (35). This is in contrast to mammalian receptors, which can bind Tf from various sources (27).…”
Section: Discussionmentioning
confidence: 93%
“…It has been shown that meningococcal transferrin receptors bind hTf specifically and fail to bind transferrin from other sources (35). In an attempt to determine whether this specificity was characteristic for both N and C lobes of TbpB, the different fusion proteins were tested for their ability to bind HRP-mTf.…”
Section: Resultsmentioning
confidence: 99%
“…However, infection in these animals does not lead to extensive infection or to rash development 12,13 . Other animal models that have been described for the bacteremia aspect of Neisseria infection take into account the bacterial preference for human transferrin as an iron source 14,15 . Either supplementing human transferrin or expressing it from a transgene results in an increased bacterial load in the blood stream over an extended time period, but this model shows no bacterial adhesion or rash development 16,17 .…”
mentioning
confidence: 99%